HUBUNGAN GAYA HIDUP SEHAT DENGAN KEJADIAN PREMENSTRUASI SYNDROME (PMS) PADA SISWI UPTD SMPN 5 BARRU - yudiarsi eppang (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2023)
Background: Premenstrual syndrome (PMS) is a physical, psychological symptom starting in the luteal phase of the menstrual cycle which occurs to a certain degree can affect lifestyle. The purpose of knowing the relationship between a healthy lifestyle and the incidence of premenstrual syndrome (PMS) in UPTD SMPN 5 Barru students. Methods: In this research is an analytic survey with a cross sectional study approach. Sampling was carried out using purpusive sampling technique. The number of samples in this study were 44 samples. Results: The results showed that the value of p = 0.001 < ? = 0.05, that there was a significant relationship between a healthy lifestyle and the incidence of premenstrual syndrome (PMS) in UPTD SMPN 5 Barru students. Conclusion: Based on the Chi Square statistical test, it was found that there was a relationship between a healthy lifestyle and the incidence of premenstrual syndrome (PMS) in UPTD SMPN 5 Barru students. It is recommended that respondents regulate healthy lifestyles such as eating nutritious food, getting enough rest, exercising, and future researchers to examine other variables that have not been studied with a larger sample